2019
DOI: 10.1016/j.celrep.2019.06.066
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Analysis Suggests that Ongoing Affinity Maturation Drives the Emergence of Pemphigus Vulgaris Autoimmune Disease

Abstract: SUMMARY Pemphigus vulgaris (PV) is an autoimmune disease characterized by blistering sores on skin and mucosal membranes, caused by autoantibodies primarily targeting the cellular adhesion protein, desmoglein-3 (Dsg3). To better understand how Dsg3-specific autoantibodies develop and cause disease in humans, we performed a cross-sectional study of PV patients before and after treatment to track relevant cellular responses underlying disease pathogenesis, and we provide an in-depth analysis of two pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 91 publications
0
19
0
Order By: Relevance
“…Examples include viral infections ( Bonsignori et al, 2018 ; Corti et al, 2010 , 2011 ; Pappas et al, 2014 ) and responses to influenza hemagglutinin, wherein unmutated revertants of virus antigen–specific mAbs, in some instances, demonstrate binding activity. These scenarios, however, must be carefully considered, as there are some limited examples of binding by germline-reverted autoantibodies ( Cho et al, 2019 ; Wenke et al, 2019 ). These collective findings may point toward the limitations of the approaches available to measure antibody–antigen interactions, including ELISAs and live CBAs, neither of which may be sufficiently sensitive to measure low-affinity interactions or accurately emulate the antigen/autoantigen binding to the BCR of naive B cells in situ, such as lymphoid tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Examples include viral infections ( Bonsignori et al, 2018 ; Corti et al, 2010 , 2011 ; Pappas et al, 2014 ) and responses to influenza hemagglutinin, wherein unmutated revertants of virus antigen–specific mAbs, in some instances, demonstrate binding activity. These scenarios, however, must be carefully considered, as there are some limited examples of binding by germline-reverted autoantibodies ( Cho et al, 2019 ; Wenke et al, 2019 ). These collective findings may point toward the limitations of the approaches available to measure antibody–antigen interactions, including ELISAs and live CBAs, neither of which may be sufficiently sensitive to measure low-affinity interactions or accurately emulate the antigen/autoantigen binding to the BCR of naive B cells in situ, such as lymphoid tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Whatever the mechanism, inhibition of SHM and affinity maturation would inhibit production of highly specific antibodies, which may be an important aspect of how MHV68 suppresses the specific antibody response. It has been shown that highly specific, broadly neutralizing antibodies to HIV [43], as well as autoantibodies cloned from systemic lupus erythematosus patients [44] and pemphigus vulgaris patients [45], lose specificity upon reversion to their germline sequence. Furthermore, this data suggests that SHM may not be a good indicator to distinguish shortlived, extra-follicular plasma cells from germinal center derived, long-lived plasma cells induced during gammaherpesvirus infection.…”
Section: Plos Pathogensmentioning
confidence: 99%
“…However, other isotypes may also be pathogenic in some variants or circumstances (Payne et al, 2005;Saleh et al, 2015). Interesting new data have revealed that DSG3-specific memory B cells have an activated phenotype and show signs of ongoing affinity maturation and clonal selection (Cho et al, 2019).…”
Section: Autoimmune Pathways and Processes In Pemphigus Autoantibodiesmentioning
confidence: 99%